The Secretion of Oxygen into the Swim-Bladder of Fish : III. The role of carbon dioxide - Wittenberg, Jonathan B. (The Rockefeller University Press, 1964)
The secretion of carbon dioxide accompanying the secretion of oxygen into the swim-bladder of the bluefish is examined in order to distinguish among several theories which have been proposed to describe the operation of the rete mirabile, a vascular countercurrent exchange organ. Carbon dioxide may comprise 27 per cent of the gas secreted, corresponding to a partial pressure of 275 mm Hg. This is greater than the partial pressure that would be generated by acidifying arterial blood (about 55 mm Hg). The rate of secretion is very much greater than the probable rate of metabolic formation of carbon dioxide in the gas-secreting complex. It is approximately equivalent to the probable rate of glycolytic generation of lactic acid in the gas gland. It is concluded that carbon dioxide brought into the swim-bladder is liberated from blood by the addition of lactic acid. The rete mirabile must act to multiply the primary partial pressure of carbon dioxide produced by acidification of the blood. The function of the rete mirabile as a countercurrent multiplier has been proposed by Kuhn, W., Ramel, A., Kuhn, H. J., and Marti, E., Experientia, 1963, 19, 497. Our findings provide strong support for their theory. The unique structure of the gas-secreting complex of the swim-bladder of the bluefish, Pomatomus saltatrix L., is described.